Enkele aspekte van die kommunikasie van verkeersveiligheid aan kinders in Suid-Afrika - H.J. Groenewald; E. Bornman (Communicare)
THE communication of current affairs like road safety in the mass media create some problems in multicultural societies like South Africa. In order to evaluate the campaigns in the mass media and the schools during Road Safety Year 1984, two surveys among Black, Coloured, Indian and White children between the ages of 10 and 17 years were undertaken by the HSRC in cooperation with The National Road Safety Council. The first survey was conducted prior to the commencement of Road Safety Year 1984 and the second during Septem- ber 1984. The results show that there is vast differences between the children of the vari- ous population groups with regard to their knowledge of subjects related to road safety and their sources of formal and infor- mal education in this regard. It appears that the electronic media reaches larger audi- ences than the print media.